HUBUNGAN KARAKTERISTIK PASIEN DENGAN TINGKAT KEPUASAN PENYAJIAN MAKANAN (STUDI DI RUANG ISOLASI COVID-19 RUMAH SAKIT ISLAM SURABAYA A. YANI) - Putri Rohma Romadloni (Jurnal Medika Hutama, 2022)
The spike in Covid-19 cases has created a challenge for health services, especially hospitals, in accepting Covid-19 patients, so this has resulted in hospitals collapsing and being overwhelmed to provide good services, so speedy handling and accuracy of nutrition for Covid-19 patients is needed. This study aims to analyze the relationship between patient characteristics and the level of satisfaction in serving food in the Covid-19 isolation room of the Surabaya A. Yani Islamic Hospital in 2021. This study is an analytical study with a quantitative approach with a cross sectional design with secondary data sources obtained from the nutrition unit of the Hospital. Islam Surabaya A. Yani. The sample of this study obtained 63 samples from a total population of 147 by taking simple random sampling. Analysis of the data used is univariate and bivariate analysis using Chi Square test to see the frequency distribution and cross tabulation. The results of this study indicate that the characteristics of patients with a level of satisfaction with food serving based on age obtained P value (0.723) > (0.05), based on gender, P value (0.436) > (0.05), based on length of stay, P value (0.077) was obtained. ) > (0.05). The conclusions from the results of this study indicate that there is no relationship between patient characteristics (age, gender, length of stay) with the level of satisfaction in serving food in the Covid-19 isolation room of the Islamic Hospital Surabaya A. Yani.